Dysregulation of Neuronal Calcium Signaling via Store-Operated Channels in Huntington's Disease - Czeredys, Magdalena (Frontiers in Cell and Developmental Biology, 2020)
Huntington's disease (HD) is a progressive neurodegenerative disorder that is characterized by motor, cognitive, and psychiatric problems. It is caused by a polyglutamine expansion in the huntingtin protein that leads to striatal degeneration via the transcriptional dysregulation of several genes, including genes that are involved in the calcium (Ca2+) signalosome. Recent research has shown that one of the major Ca2+ signaling pathways, store-operated Ca2+ entry (SOCE), is significantly elevated in HD. SOCE refers to Ca2+ flow into cells in response to the depletion of endoplasmic reticulum Ca2+ stores. The dysregulation of Ca2+ homeostasis is postulated to be a cause of HD progression because the SOCE pathway is indirectly and abnormally activated by mutant huntingtin (HTT) in -aminobutyric acid (GABA)ergic medium spiny neurons (MSNs) from the striatum in HD models before the first symptoms of the disease appear. The present review summarizes recent studies that revealed a relationship between HD pathology and elevations of SOCE in different models of HD, including YAC128 mice (a transgenic model of HD), cellular HD models, and induced pluripotent stem cell (iPSC)-based GABAergic medium spiny neurons (MSNs) that are obtained from adult HD patient fibroblasts. SOCE in MSNs was shown to be mediated by currents through at least two different channel groups, Ca2+ release-activated Ca2+ current (ICRAC) and store-operated Ca2+ current (ISOC), which are composed of stromal interaction molecule (STIM) proteins and Orai or transient receptor potential channel (TRPC) channels. Their role under physiological and pathological conditions in HD are discussed. The role of Huntingtin-associated protein 1 isoform A in elevations of SOCE in HD MSNs and potential compounds that may stabilize elevations of SOCE in HD are also summarized. Evidence is presented that shows that the dysregulation of molecular components of SOCE or pathways upstream of SOCE in HD MSN neurons is a hallmark of HD, and these changes could lead to HD pathology, making them potential therapeutic targets.